Pengaruh Minat Terhadap Hasil Belajar IPS Siswa - Mai Sri Lena; Sahrun Nisa; Tiara Maisy; Dani Anisa Imanda (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to determine the effect of interest on social studies learning outcomes of students. This type of research is classified into ex post facto research using a quantitative approach. This research was carried out in several elementary schools by using a questionnaire (questionnaire) to obtain variable data on interest in learning. The variables in this study consist of two, namely the independent variable and the dependent variable. The population in this study were all students of grades IV, V and IV of elementary school. The sampling technique was carried out by random sampling. Based on the results of research, educators or teachers are expected to be able to provide motivation and reinforcement in the learning process so that students are interested in participating in learning and studying seriously.